2014
DOI: 10.9790/3008-09335461
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ginger and Thyme on Some Biochemical Parameters in Diabetic Rats

Abstract: Diabetes mellitus (DM) is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…The reduction of TC and TG were also reported by 15 [ 21 , 26 , 29 , 30 , 34 , 35 , 38 , 41 , 44 , 49 , 52 , 54 , 56 , 59 , 60 ] and 14 [ 21 , 26 , 29 , 30 , 34 , 35 , 38 , 41 , 44 , 49 , 52 , 56 , 59 , 60 ] studies respectively. Ginger has been shown to improve low-density lipoprotein-cholesterol (LDL-C) [ 26 , 29 , 30 , 35 , 38 , 52 , 54 , 56 , 59 ] and high-density lipoprotein-cholesterol (HDL-C) [ 26 , 29 , 30 , 35 , 38 , 49 , 56 , 59 , 60 ] levels in nine studies. One study reported contradictory results for TC, TG, and LDL-C, as well as two studies for HDL-C [ 23 , 44 ].…”
Section: Resultssupporting
confidence: 52%
See 3 more Smart Citations
“…The reduction of TC and TG were also reported by 15 [ 21 , 26 , 29 , 30 , 34 , 35 , 38 , 41 , 44 , 49 , 52 , 54 , 56 , 59 , 60 ] and 14 [ 21 , 26 , 29 , 30 , 34 , 35 , 38 , 41 , 44 , 49 , 52 , 56 , 59 , 60 ] studies respectively. Ginger has been shown to improve low-density lipoprotein-cholesterol (LDL-C) [ 26 , 29 , 30 , 35 , 38 , 52 , 54 , 56 , 59 ] and high-density lipoprotein-cholesterol (HDL-C) [ 26 , 29 , 30 , 35 , 38 , 49 , 56 , 59 , 60 ] levels in nine studies. One study reported contradictory results for TC, TG, and LDL-C, as well as two studies for HDL-C [ 23 , 44 ].…”
Section: Resultssupporting
confidence: 52%
“…Twenty-eight of 31 studies showed that ginger intake lowers blood glucose levels [ 24 , 25 , 27 , 29 , 30 , 34 – 43 , 47 – 49 , 51 – 53 , 55 – 61 ]. On the contrary, in 2 studies, blood glucose levels increased [ 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Promising results in terms of antidiabetic activity of thyme have been observed in both streptozotocin [ 13 ] and alloxan models [ 48 ] of diabetes mellitus in rats, suggesting its potential use in the treatment of metabolic syndrome. The intake of thyme extract managed to reduce serum concentrations of cholesterol and triglycerides, but we did not observe these effects.…”
Section: Discussionmentioning
confidence: 99%